Pengaruh Empati dan Dukungan Sosial Terhadap Intensi Berwirausaha Sosial Dimoderasi Oleh Pendidikan Kewirausahaan - Ardhaneswari, Wahya; Sabandi, Muhammad; Octoria, Dini (Jurnal Pendidikan Ekonomi (JUPE), 2024)
Social entrepreneurship is an important and interesting thing to discuss because there are still few studies in the field of entrepreneurship that discuss social entrepreneurship. This study aims to determine how the influence of empathy and social support on social entrepreneurial intentions moderated by entrepreneurship education variables. This research is a quantitative study using survey method with the research population is Diploma and Strata-1 students of Sebelas Maret University. The sample set as many as 271 samples and taken using purposive sampling technique. Data were collected through a 1-5 point Likert scale online questionnaire distributed through google forms. Data analysis was carried out using Moderated Regression Analysis with SmartPLS software. The results prove that there is an influence of empathy and there is an influence of social support on the intention of social entrepreneurship. In addition, entrepreneurship education strengthens the relationship between empathy and the relationship between social support to social entrepreneurship intention.